Carburized steel part
By incorporating a ferrite and martensite composite structure in the non-carburized portion of carburized steel parts, the strain-induced issues in gear components are mitigated, resulting in improved fatigue life and reduced vibration and noise.
Patent Information
- Application Number
- JP2024141232
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-19
- Filing Date
- 2024-08-22
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-08-22
AI Technical Summary
Existing carburized steel parts used in automotive and construction machinery suffer from strain-induced issues such as vibration, noise, and reduced fatigue life, particularly in gear portions, due to heat treatment strain.
The carburized steel part is designed with a non-carburized portion that has a composite structure of ferrite and martensite, with a ferrite area ratio of 0.5 to 45.0% and specific grain structure characteristics to uniformly disperse ferrite grains and effectively absorb strain.
This approach significantly reduces strain in carburized steel parts, particularly in gear components, thereby enhancing gear quietness, miniaturization, and extending the fatigue life of the parts.
Smart Images

Figure 2025044138000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to carburized steel parts (including gas carburized and vacuum carburized) used in the fields of construction industry machinery and automobiles. [Background technology]
[0002] Power transmission parts such as differential gears and gear shafts used in automobiles and construction machinery use alloy steels for machine structures, including JIS standard SCr420 and SCM420.
[0003] The method for producing such an alloy steel for machine structure is outlined as follows. That is, steel bars and wire rods made from alloy steel for mechanical structures are roughly formed into the part shape by hot and / or cold forging, and then finely formed by cutting. After that, they are subjected to surface hardening treatments such as induction hardening and tempering (induction heat treatment) or gas / vacuum carburizing quenching and tempering (carburizing heat treatment) to produce the final product. In the induction heat treatment and carburizing heat treatment, the steel is heated to 900°C or higher, held there, and then cooled, causing a transformation in the steel structure to harden the component. Therefore, heat treatment distortion occurs due to the transformation of the steel structure during heating.
[0004] In particular, in parts with gears, poor meshing due to distortion leads to vibration, noise, and shortened fatigue life of the gears. Therefore, a grinding and straightening process is required depending on the degree of distortion, which leads to increased costs.
[0005] To address such issues, for example, the techniques described in the following Patent Documents 1 to 3 have been proposed. That is, Patent Document 1 proposes a technology relating to steel and gears in which the structure in the non-carburized parts of the parts is made into a composite structure of ferrite and martensite, thereby reducing distortion and improving root bending and surface fatigue properties.
[0006] Patent Document 2 proposes a technology for carburized steel parts in which the structure in the non-carburized parts of the parts is a composite structure of ferrite and martensite, and the ferrite grain size is controlled to reduce strain and improve fatigue properties.
[0007] Patent Document 3 proposes a technology for carburized steel parts in which the structure in the non-carburized parts is made a composite structure of ferrite and martensite, and nitriding treatment is performed before carburizing and quenching, thereby reducing distortion and improving surface fatigue properties. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2002-121645 A [Patent Document 2] JP 2003-129171 A [Patent Document 3] JP 2013-112827 A Summary of the Invention [Problem to be solved by the invention]
[0009] As described in Patent Documents 1 to 3, ferrite phase precipitation in non-carburized parts is effective in reducing strain in carburized heat-treated steel parts. That is, the relatively soft ferrite phase absorbs the strain during martensitic transformation, thereby reducing strain.
[0010] However, in recent years, with the electrification of automobiles, there has been a greater need to reduce distortion in carburized steel parts than ever before in order to make gears quieter and more compact.
[0011] The present invention has been made in consideration of the above circumstances, and has an object to provide a carburized steel part which reduces distortion after carburizing heat treatment, thereby eliminating the problem of poor meshing, particularly in parts having gear portions. [Means for solving the problem]
[0012] The present inventors have investigated the effect of the structure of steel parts on distortion after carburizing heat treatment in order to realize a reduction in distortion in members after carburizing heat treatment.
[0013] As a result, we have come to the realization that it is important that the structure of the non-carburized portion after carburizing heat treatment is a composite structure of ferrite and martensite, with the ferrite phase precipitating as uniformly as possible.
[0014] The present invention has been completed based on the above findings. That is, the gist of the present invention is as follows. 1. A carburized steel part having a carburized portion and a non-carburized portion, the structure of the non-carburized portion having a ferrite area ratio of 0.5 to 45.0%, the maximum area of the group of ferrite grains and adjacent ferrite grains (ferrite grain group) being 30.0% or less of the total area of the ferrite grains in the non-carburized portion, and the ratio of the length of the boundary of the ferrite grain group that is in contact with ferrite grains not belonging to the ferrite grain group to the total length of the boundary perimeter of the ferrite grain group is 50.0% or less. Effect of the Invention
[0015] According to the present invention, it is possible to provide a carburized steel part in which the distortion caused by the carburizing heat treatment is reduced. In particular, since the reduction in distortion is realized in a carburized steel part having a gear portion, it is possible to suppress the meshing failure in this type of carburized steel part. [Brief description of the drawings]
[0016] [Figure 1] FIG. 1 is a diagram showing the relationship between the ferrite area ratio and the rotating bending fatigue life. [Diagram 2] FIG. 13 is a diagram showing the relationship between the ferrite area ratio and the amount of core runout. [Diagram 3]FIG. 1 is a conceptual diagram showing a group (ferrite grain group) of ferrite grains and ferrite grains adjacent to the grains in the present invention, and the ratio of the length of the boundary of the ferrite grain group that is in contact with ferrite grains that do not belong to the ferrite grain group to the length of the entire perimeter of the boundary of the ferrite grain group. [Figure 4] FIG. 2 is a diagram showing the shape of a rotating bending fatigue test piece. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] Hereinafter, an embodiment of the present invention will be described in detail.
[0018] [Non-carburized part] The carburized steel parts of the present invention are made by subjecting a molded body into the shape of the part to a carburizing heat treatment of carburizing, quenching and tempering. As a result, carbon penetrates into the steel from the surface, forming a carburized part on the part surface with an increased carbon content compared to before the carburizing heat treatment. On the other hand, there are also non-carburized parts where no carbon has penetrated due to the carburizing heat treatment and where the carbon content is the same as before the carburizing heat treatment. In other words, the carburized and non-carburized parts have different carbon contents, and such non-carburized parts contain less carbon than the carburized parts, so it is possible to distinguish between them by measuring Vickers hardness.
[0019] [The structure of the non-carburized area has a ferrite area ratio of 0.5 to 45.0%] By setting the area ratio of ferrite in the non-carburized portion within the range of 0.5 to 45.0%, it is possible to suppress distortion while maintaining excellent fatigue properties, which are important for carburized steel parts.
[0020] The relationship between the area ratio of ferrite in the structure of the non-carburized portion (ferrite area ratio) and the rotating bending fatigue properties and the core runout in the examples described later are shown in Figures 1 and 2, respectively. The rotating bending fatigue properties were measured as an evaluation index for fatigue properties, and the core runout was measured as an evaluation index for strain.
[0021] As shown in Figure 1, when the ferrite area ratio in the non-carburized portion exceeds 45.0%, the rotating bending fatigue life is significantly reduced. On the other hand, as shown in Figure 2, when the ferrite area ratio in the non-carburized portion is below 0.5%, no effect of reducing strain can be expected. Therefore, in the present invention, the ferrite area ratio in the non-carburized portion is set in the range of 0.5 to 45.0%. In the present invention, the remaining structure of the non-carburized portion is considered to be mainly martensite (in an area ratio of about 50 to 90%). In addition, any structure such as bainite or retained austenite that is found in known carburized steel parts may be present as long as it accounts for about 0 to 40% of the remaining structure in area ratio.
[0022] Here, the ferrite area ratio can be obtained by corroding and observing the part after the carburizing heat treatment appropriately. For example, after corroding with a nital solution to make ferrite grains visible, the composite structure of ferrite and martensite is photographed, and the ferrite area ratio can be obtained by image processing software.
[0023] The ferrite area ratio of the non-carburized part of the carburized steel part is preferably determined by observing the non-carburized part in any ten visual fields at a magnification of 400 times using an optical microscope, for example, because the ferrite area ratio of the non-carburized part determined by such observation can be said to represent the whole.
[0024] [The maximum area of a group of ferrite grains and adjacent ferrite grains (ferrite grain group) is 30.0% or less of the total area of the ferrite grains in the non-carburized portion, and the ratio of the length of the boundary of the ferrite grain group that is in contact with ferrite grains not belonging to the ferrite grain group to the total length of the boundary perimeter of the ferrite grain group is 50.0% or less] The above-mentioned requirement for the ferrite grains of the present invention is an index showing the properties of the ferrite grains that can further enhance the effect of reducing distortion after carburizing heat treatment. In Fig. 2, which shows the relationship between the ferrite area ratio and the amount of distortion in the non-carburized part, the ones that satisfy the above-mentioned requirement are shown as white plots (examples of the invention) in Fig. 2. As shown in FIG. 2, when this regulation is satisfied, the distortion is reduced more effectively, and the effect of the present invention is obtained.
[0025] FIG. 3 is a conceptual diagram showing a group of ferrite grains and ferrite grains adjacent to the ferrite grains (ferrite grain group) in the present invention, the length of the entire boundary circumference of the ferrite grain group, and the length of the boundary of the ferrite grain group that is in contact with ferrite grains that do not belong to the ferrite grain group. In Fig. 3, the figures enclosed in circles are ferrite grains. The white parts within the frames are the remaining structures other than ferrite. The frames are randomly selected from the non-carburized parts, and the size of each frame is preferably about 200 x 300 µm. As in the examples described later, observing the frames in 10 fields of view at 400x magnification is sufficient to confirm the effect of the present invention. JPEG2025044138000002.jpg28170
[0026] 3 are boundaries of ferrite grains that are in contact with ferrite grains that do not belong to the ferrite grain group, and thick lines are boundaries of ferrite grains that are in contact with remaining structures other than ferrite. In other words, the length of the entire circumference of the boundary of the ferrite grain group is the sum of the lengths of the dotted lines and the thick lines. Therefore, the ratio of the length of the boundary of the ferrite grain group that is in contact with ferrite grains not belonging to the ferrite grain group to the length of the entire boundary perimeter between the ferrite grain group and the ferrite grain group in the present invention (also referred to simply as the "boundary length ratio" in the present invention) is the percentage obtained by dividing the length of the dotted line in FIG. 3 by the total length of the dotted line and the thick line.
[0027] Here, in the present invention, the area of the ferrite grain group, the total area of the ferrite grains, and the boundary length ratio can be determined by appropriately corroding and observing the part after the carburizing heat treatment. JPEG2025044138000003.jpg64170 Furthermore, the length of the entire boundary perimeter of a ferrite grain group and the length of the boundary of the ferrite grain group that is in contact with ferrite grains that do not belong to the ferrite grain group can also be determined in the same manner as the area, and the boundary length ratio can be determined by using the percentage of the value obtained by dividing the value of the boundary length by the value of the entire boundary perimeter.
[0028] In the present invention, it is essential that the area ratio using the maximum area of the ferrite grain group is 30.0% or less of the total area of the ferrite grains, and that the boundary length ratio is 50.0% or less. In other words, the area of each group of adjacent ferrite grains (ferrite grain group) is 30.0% or less of the total area of the ferrite grains at most, and more than 50.0% of the boundaries in the ferrite grain group must be in contact with structures other than ferrite grains. Satisfying these requirements is because, as mentioned above, it provides a better strain reduction effect.
[0029] JPEG2025044138000004.jpg21170Further, the ferrite grain group in the present invention means a group of a plurality of ferrite grains, which does not contain other structures such as martensite, as shown in Fig. 3. Therefore, for example, it may be a group consisting of two or more ferrite grains, or 3 to 5 or more ferrite grains.
[0030] The present invention achieves the effect of reducing strain by controlling the structural composition in the non-carburized portions of parts after carburizing heat treatment, i.e., by uniformly dispersing ferrite grains and effectively absorbing the strain caused by martensitic transformation.
[0031] Therefore, in the present invention, the carburizing and quenching is performed at a temperature where the two-phase region of ferrite and austenite exists, and the composition of the steel used is not particularly specified as long as the non-carburized part after the carburizing and quenching has an area ratio of 0.5% or more of ferrite. Note that, if the composition elements are those used in known carburized parts, the two-phase region of ferrite and austenite is in the range of 750 to 900°C.
[0032] In addition, a composition system in which the two-phase region of ferrite and austenite exists over a wide range and at high temperatures is preferable for manufacturing parts because the restrictions on the heat treatment process are relaxed. Therefore, the following are examples of suitable composition ranges for part materials. Any other component elements used in known carburized steel parts may be suitably used as long as they satisfy the above-mentioned requirements for the steel structure. The balance of the steel components is Fe and impurities. These impurities are those that are mixed in from raw materials such as ore and scrap, or from the manufacturing environment, during industrial production of steel, and are permissible within a range that does not adversely affect the characteristics of this embodiment.
[0033] C is an ingredient that has a large effect on the two-phase region of ferrite and austenite, and as it increases, it reduces the two-phase region, so the preferred range of C is 0.10 to 0.60 mass%.
[0034] Like C, Si is an ingredient that greatly affects the two-phase region of ferrite and austenite, and increases the two-phase region. On the other hand, if the Si content is too high, the formability of parts decreases. Therefore, the preferable range is 0.10 to 2.50 mass%.
[0035] Carburized steel parts are generally manufactured by the process described below. In other words, the steel material is cold / hot forged to produce an intermediate product, which is then cold worked to give it the shape of the product. After the desired shape is obtained, the carburizing heat treatment is performed to complete the process. In the present invention, it is particularly important to carry out a process in which the steel is cooled and held at the low temperature side of the ferrite / austenite two-phase region under specified conditions at least once after the carburizing treatment and before quenching, so that the ferrite grains in the non-carburized portion after carburizing and quenching are within the range of the present invention described above. For example, one example of the specified conditions is to hold the steel at the low temperature side of the two-phase region for 30 minutes, and then raise the temperature by 20°C or more and hold the steel for an additional 5 to 30 minutes. In this way, by combining holding the temperature at 20°C or more from the low temperature side of the two-phase region, it is possible to satisfy the conditions necessary for achieving the effects of the present application (the maximum area of a group of ferrite grains and ferrite grains adjacent to said grains (ferrite grain group) is 30.0% or less of the total area of the ferrite grains in the non-carburized portion, and the ratio of the length of the boundary of the ferrite grain group that is in contact with ferrite grains not belonging to the ferrite grain group to the length of the entire perimeter of the boundary of the ferrite grain group is 50.0% or less).
[0036] In the carburized steel parts and manufacturing methods thereof described in this specification, any items not described in this specification can use publicly known regulations and manufacturing methods for carburized steel parts. EXAMPLES
[0037] The configuration and effects of the present invention will be specifically described below with reference to examples. However, the present invention is not limited to the following examples, and appropriate modifications can be made within the scope of the gist of the present invention, and all of these are included in the technical scope of the present invention.
[0038] Steel with the composition shown in Table 1 (balance: Fe and impurities) was melted and hot rolled into round bars with a diameter of 36 mm. Rotating bending fatigue test specimens (round bars) shown in Figure 4 were taken from these round bars. The test specimens were subjected to carburizing heat treatment to prepare evaluation test specimens. In this embodiment, the quenching temperature and the holding time at the quenching temperature in the carburizing heat treatment were adjusted in order to obtain an appropriate structural structure in the non-carburized portion. That is, after heating to the austenite single phase region, the material was cooled to the low temperature side of the ferrite / austenite two-phase region (for example, 750 to 850°C) before quenching and held for 30 minutes (first stage), and then held at a temperature in the ferrite / austenite two-phase region (for example, 770 to 900°C), which is 20°C or more higher than the first stage holding temperature, for 5 to 30 minutes (second stage), and then quenching was performed. In addition, as comparative examples, samples were also prepared by simply holding the material from the austenite single phase region to the ferrite / austenite two-phase region (for example, 750 to 900°C) in one step for 10 to 30 minutes before quenching, and then quenching (Test Nos. 41 to 45).
[0039] In this way, by holding the steel at the low temperature side of the ferrite / austenite two-phase region before quenching, the number of nucleation sites for ferrite grains is increased, and the subsequent holding at the high temperature side makes it easier to uniformly disperse the ferrite grains. Since the ferrite / austenite two-phase region varies depending on the steel composition, the transformation point can be found by a transformation point measurement test (formaster test) or the like, and the quenching temperature and the holding time at the quenching temperature can be adjusted according to that temperature to obtain an appropriate structural composition.
[0040] [Table 1]
[0041] [Identification of non-carburized areas] The non-carburized region was identified by measuring the hardness of the test piece. That is, the hardness was measured by cutting the test piece in parallel to the diameter direction after the carburizing heat treatment, and measuring the Vickers hardness at 0.2 mm pitch from the surface at 300 gf. By measuring the hardness in the diameter direction from the sample surface, the region where the Vickers hardness was less than 550 HV was identified as the non-carburized region.
[0042] Using the test pieces after the carburizing heat treatment, the ferrite area fraction, the area ratio and the boundary length ratio in the structure of the non-carburized portion were investigated.
[0043] [Ferrite area ratio in the structure of non-carburized parts] The non-carburized area was observed by cutting out a sample with the observation surface being a surface parallel to the diameter direction of the round bar in the evaluation test piece. The cut out sample was corroded with 1% nital, and the ferrite and martensite composite structure in the non-carburized area identified in the hardness measurement described above was photographed at 400x magnification in 10 randomly selected fields of view using an optical microscope. The ferrite grains were traced based on the photographs, and the traced images were processed using the image processing software ImageJ to separate each ferrite grain and calculate its area. From the obtained ferrite grain area data, the area ratio of each field of view to the entire field of view was calculated, and this was taken as the ferrite area ratio in the non-carburized part.
[0044] [Maximum ratio of the above area ratio] Using the area of each ferrite grain obtained in the same manner as above, the total area of the ferrite grains and the maximum area of the ferrite grain group were calculated, and the ratio between them was determined.
[0045] [Evaluation of the maximum value of the boundary length ratio] Based on the photographs taken as described above, each ferrite grain group was traced, and the traced image was processed using image software ImageJ to measure the length of the entire boundary circumference of the ferrite grain group and the length of the boundary of the ferrite grain group where the ferrite grain group contacts with ferrite grains in the non-carburized region not belonging to the ferrite grain group. For each field of view, the ratio of the length of the boundary of the ferrite grain group where the ferrite grain group contacts with ferrite grains in the non-carburized region not belonging to the ferrite grain group to the entire boundary circumference of the ferrite grain group was calculated, and the maximum value was evaluated.
[0046] Furthermore, the test pieces after the carburizing heat treatment were evaluated for rotating bending fatigue life and core runout in the following manner. [Rotating bending fatigue life] The rotating bending fatigue life was measured using an Ono-type rotating bending fatigue tester. The test was performed at a rotation speed of 3600 rpm with a load stress of 600 MPa, and the number of repetitions until destruction was measured. In this test, if a fracture life of 2.00E+06 or more is shown, it can be said that the material has sufficient fatigue properties.
[0047] [Test piece runout] The distortion after carburizing heat treatment was measured with an eccentricity tester. That is, by supporting holes drilled at the center of both ends of the test piece before carburizing heat treatment, the displacement width (difference between maximum and minimum displacement) when the test piece part after carburizing heat treatment was rotated in the circumferential direction was measured with a micrometer. In this test, if the core runout was 35 mm or less, it can be said that the distortion of the carburized steel part is sufficiently suppressed.
[0048] The test results are shown in Table 2. Figures 1 and 2 show the relationship between the ferrite area ratio of the non-carburized part and the rotating bending fatigue properties and the relationship with runout, respectively. Note that Figure 2 shows only examples where the fatigue life is within the suitable range.
[0049] [Table 2]
[0050] As shown in Table 2, all of the examples according to the present invention have sufficient fatigue properties and distortion is sufficiently suppressed, which makes it possible to achieve quieter and more compact gears.
Claims
[Claim 1] A steel sheet has a carburized portion and a non-carburized portion, and the structure of the non-carburized portion has a ferrite structure with an area ratio of 0.5 to 45.0%, The ferrite has a maximum area of a group of ferrite grains and adjacent ferrite grains (ferrite grain group) of 30.0% or less of the total area of ferrite grains in the non-carburized portion, and the ratio of the length of the boundary of the ferrite grain group that is in contact with ferrite grains not belonging to the ferrite grain group to the length of the entire perimeter of the boundary of the ferrite grain group is 50.0% or less. Carburized steel parts.
Citation Information
Patent Citations
Case hardening steel for gears
EP0769566A1
JP1975152933A
Quenching method for preventing heat treating strain in case hardening steel
JP1999036060A
Low distortion steel for gear, excellent in pitting resistance, and manufacture of gear using the steel
JP2001032037A
High fatigue-strength carburized steel parts
JP2003129171A